Replacement of A Hopeless Mandibular Tooth With an Immediately Placed and Loaded Dental Implant : A Case Report - Farhan Raza Khan; Sadia Tabassum (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Immediate implants have gained a wide popularity in the recent times as patients benefit from reduced time interval between the implant placement and delivery of the final restoration.Careful treatment planning and execution of the procedure can prevent the need to undergo second stage surgery for prosthesis and thus improves the patients' compliance. An immediate placement and loading protocol has been followed in this case report.